Transaction costs of SHG lending-impact on branch viability - Srinivasan, Girija; Satish, P.; Bankers Institute of Rural Development (Lucknow : Bankers Institute of Rural Development, 2000)
Study with reference to India.
Includes statistical tables.
Includes bibliographical references (p. 117).
Keywords: Rural credit -- India -- Case studies; Rural credit -- India -- Statistics; Self-help groups -- India -- Case studies; Banks and banking -- India -- Case studies